Literacy assessment : helping teachers plan instruction - Cooper, J. David (Unites States of America : Houghton Mifflin Company, 2008)
This text reflects our lifelong dedication to helping teachers effectively help all children become literate.
Part One. Tools and Techniques for Assessment-Based Literacy Instruction -- Part Two. Literacy Stages: Assessment and Instruction -- Part Three. Beyond the Classroom .
Includes bibliographical references and index.
Keywords: LESSON PLANNING